Coccidioidomycosis: skin manifestations and hypersensitivity syndromes - Mejia, Melisa; Cardona Castro, Nora (CES Medicina, 2016)
Coccidioidomycosis is caused by Coccidioides immitis and Coccidioides posadasii fungi, which are endemic in certain locations in the American continent. They produce an asymptomatic infection in the majority of the exposed population, and in a lower proportion, a self-limited influenza-like illness, pneumonia or dissemination. Skin compromise could be secondary to the infection by the fungus or by a hypersensitivity reaction to the pulmonary infection. Primary skin compromise produces a chancriform, self-limited lesion, and the dissemination to the skin commonly produces nodules and abscesses, with a tendency to form fistulas. The most common hypersensitivity reaction is erythema nodosum, which is considered a marker of good prognosis. Treatment depends on the localization of the infection, the presence of dissemination, and the clinical conditions of the patient. DOI: http://dx.doi.org/10.21615/cesmedicina.30.2.6